1999
DOI: 10.1034/j.1600-0501.1999.100609.x
|View full text |Cite
|
Sign up to set email alerts
|

Sinus floor augmentation with simultaneous placement of dental implants using a combination of deproteinized bone xenografts and recombinant human osteogenic protein‐l. A histometric study in miniature pigs.

Abstract: Maxillary sinus floor augmentation with autogenous bone has become a widely accepted procedure in implant dentistry. The use of osteoconductive bone substitutes in this indication is controversial, since their use can lead to a prolonged healing time, inhomogenous ossification, foreign body reaction, migration of particles and low bone-implant contact (BIC). The purpose of this study was to examine whether the combination of an osteoinductive protein (recombinant human osteogenic protein-1 (rhOP-1 = bone morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
137
0
17

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(159 citation statements)
references
References 0 publications
5
137
0
17
Order By: Relevance
“…BMPs) which have osteogenic and osseoconductive effects (Rahn and Perren, 1970;Rahn, 1976;Allegrini et al, 2003). The osseoinductive effect of rhBMP-2 depends on the amount of cells in the region of augmentation which in turn depends on the species, the age and the vascularity of the area (Terheyden et al, 1999;Yamaji et al, 2007). Sinus-lift procedures in a sheep model are a reliable method for evaluating bone formation (Aral et al, 2008;Estaca et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BMPs) which have osteogenic and osseoconductive effects (Rahn and Perren, 1970;Rahn, 1976;Allegrini et al, 2003). The osseoinductive effect of rhBMP-2 depends on the amount of cells in the region of augmentation which in turn depends on the species, the age and the vascularity of the area (Terheyden et al, 1999;Yamaji et al, 2007). Sinus-lift procedures in a sheep model are a reliable method for evaluating bone formation (Aral et al, 2008;Estaca et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…During this study a total of 0.8 mg rhBMP-2 in a concentration of 0.4 mg/ml was used while Terheyden et al (1999) and Roldán et al 2004 used a concentration of 0.4 mg/ml rhBMP-7 for their study on mini pigs, normal bone contains only 0.002 mg/kg of BMP (Rengachary, 2002). Other studies showed that large bone defects could be repaired using rhBMP-2 on a PLPG sponge (Marukawa et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydroxyapatite, biphasic tri-calcium phosphate-hydroxyapatite, and natural coral are r e p o r t e d t o b e e q u a l l y g o o d a s f r a m i n g material for bone morphogenetic protein (Pekkarinen et al, 2005). Deproteinized bovine bone mineral is known to show excellent osteoconductive properties, and it has been used for sinus augmentation clinically (Terheyden et al, 1999). The bovine xenograft composite promotes formation of new bone in a similar fashion to autogenous bone when bone morphogenetic proteins were bound to the graft material, and could therefore be considered a biomaterial with potential applications as a bone substitute in maxillary sinus floor augmentation (Sicca et al, 2008).…”
Section: Bone Morphogenetic Proteinmentioning
confidence: 99%